Jury System in France Cour de Assies: Could it be adopted in the Indonesian Criminal Court? - Tampubolon, Manotar; Intan, Nur; Boansaor, Ramos O.; Silalahi, Rivaldo P.; Savril, Daniel P.; Joshua, Christian; Asterina, Annisa F.; Nainggolan, Melda E.; Rachelia, Agnes J.; Mario, Firman; et al. (Technium Social Sciences Journal, 2021)
This qualitative article provides findings on the possibility of implementing the France Cour de Assies jury system in Indonesian criminal court. The researcher explains the reasons for adopting the jury system in the French assize court, the position of the jury, the procedure for appointing jurors, explaining the advantages of the jury. The comparative perspective allows the researchers to reveal what is less known and gain better insight into two more things: the relationship between criminal justice and public involvement in modern society; and the meaning of criminal justice. Researchers use secondary data comprising books, journals, or references about the French Cour de Assies, including legislation, judicial decisions, customs, and doctrines. The adoption of the jury system in Indonesia is essential, considering that Indonesia is a democratic country; therefore, it must include the involvement of the public in the judiciary. It is possible to involve the public in case of examination in court as a jury, which is the obligation of a democratic country. This article suggests that the jury system in the Cour de Assies France can be accepted because, in Indonesian criminal justice, it is necessary to involve the public in determining if someone is guilty.